Expression of the Reverse Transcriptase Domain of Telomerase Reverse Transcriptase Induces Lytic Cellular Response in DNA-Immunized Mice and Limits Tumorigenic and Metastatic Potential of Murine Adenocarcinoma 4T1 Cells - Juris Jansons (Vaccines, 2020)
Telomerase reverse transcriptase (TERT) is a classic tumor-associated antigen overexpressed in majority of tumors. Several TERT-based cancer vaccines are currently in clinical trials, but immune correlates of their antitumor activity remain largely unknown. Here, we characterized fine specificity and lytic potential of immune response against rat TERT in mice. BALB/c mice were primed with plasmids encoding expression-optimized hemagglutinin-tagged or nontagged TERT or empty vector and boosted with same DNA mixed with plasmid encoding firefly luciferase (Luc DNA). Injections were followed by electroporation. Photon emission from booster sites was assessed by in vivo bioluminescent imaging. Two weeks post boost, mice were sacrificed and assessed for IFN-γ, interleukin-2 (IL-2), and tumor necrosis factor alpha (TNF-α) production by T-cells upon their stimulation with TERT peptides and for anti-TERT antibodies. All TERT DNA-immunized mice developed cellular and antibody response against epitopes at the N-terminus and reverse transcriptase domain (rtTERT) of TERT. Photon emission from mice boosted with TERT/TERT-HA+Luc DNA was 100 times lower than from vector+Luc DNA-boosted controls. Bioluminescence loss correlated with percent of IFN-γ/IL-2/TNF-α producing CD8+ and CD4+ T-cells specific to rtTERT, indicating immune clearance of TERT/Luc-coexpressing cells. We made murine adenocarcinoma 4T1luc2 cells to express rtTERT by lentiviral transduction. Expression of rtTERT significantly reduced the capacity of 4T1luc2 to form tumors and metastasize in mice, while not affecting in vitro growth. Mice which rejected the tumors developed T-cell response against rtTERT and low/no response to the autoepitope of TERT. This advances rtTERT as key component of TERT-based therapeutic vaccines against cancer.